Modifikasi Mesin Penggiling Daging (Meat Grinder) Kapasitas 8 Kg Menggunakan Motor Listrik - Hilda Porawati; Ari Kurniawan (LPPM Politeknik Jambi, 2020)
Modification of meat grinder machine 8 kg capacity has been developed to get an applicable machine for fish meat processing in micro and small enterprise like that warung pempek, kemplang and crackers businesses. The machine is designed more simply that driven by AC motor 0.5 HP with speed rotation of 1400 rpm. The results using 3 types of fish shows that average capacity of machine is 12,13 kg/ hour. In addition, the element of convenience in washing the grinder blade is a major aspect to consider in modification.